A phase 1b expansion study of TAS‐102 with oxaliplatin for refractory metastatic colorectal cancer. Issue 9 (22nd December 2020) - Cecchini, Michael; Kortmansky, Jeremy S.; Cui, Can; Wei, Wei; Thumar, Jaykumar Ranchobdhai; Uboha, Nataliya V.; Hafez, Navid; Lacy, Jill; Fischbach, Neal A.; Sabbath, Kert D.; Gomez, Christina M.; Sporn, Jonathan Reed; et al.
Abstract : Background: TAS‐102, a novel antimetabolite, is approved for treatment of refractory metastatic colorectal cancer (CRC). This study sought to determine whether the addition of TAS‐102 to oxaliplatin (TAS‐OX) was safe and effective in metastatic CRC previously treated with oxaliplatin. Methods: This investigator‐initiated, open‐label, single‐arm phase 1b study enrolled patients with metastatic CRC previously treated with 5‐fluorouracil, irinotecan, and oxaliplatin. In dose escalation, TAS‐102 was given at 3 dose levels: 25, 30, and 35 mg/m 2 twice daily on day 1 to day 5 with 85 mg/m 2 oxaliplatin on day 1 in 14‐day cycles. The primary endpoint of dose escalation was the recommended dose for expansion, and in dose expansion, the primary endpoint was overall response rate (ORR) according to the Response Evaluation Criteria in Solid Tumors (RECIST, version 1.1). Results: Forty‐one patients were treated with TAS‐OX. No dose‐limiting toxicities were observed in the 11 patients treated in escalation. The recommended dose for expansion was 35 mg/m 2 TAS‐102 twice daily on day 1 to day 5 in combination with 85 mg/m 2 oxaliplatin on day 1 in 14‐day cycles. In the intention‐to‐treat population, the ORR was 2.4% (95% CI, 0%‐12.9%) with 1 of 41 patients having a partial response, although 12 (29%) had tumor shrinkage. The median progression‐free survival was 2.7 months (95% CI, 2.4‐4.8 months) and median overall survival was 6.8 months (95% CI, 5.7‐10 months). Conclusions: TAS‐OX is safe with no unexpected toxicities at standard doses of each agent. The combination did not result in a clinically meaningful ORR, although progression‐free survival and overall survival were encouraging in this heavily pretreated population. Lay Summary: For metastatic colorectal cancer, the treatment combination of TAS‐102 and oxaliplatin was found to be well‐tolerated and revealed no unexpected side effects. Twelve of 41 patients had reductions in the size of their tumor, and the study treatment delayed the time to tumor growth as opposed to what would be expected. Abstract : The combination of TAS‐102 and oxaliplatin is safe with no unexpected toxicities in treatment‐refractory metastatic colorectal cancer. Although the treatment did not reveal a robust radiographic response rate, the disease‐control and progression‐free survival rates were encouraging.